Theranostics Based on Magnetic Nanoparticles and Polymers: Intelligent Design for Efficient Diagnostics and Therapy - Gauger, Andrew J.; Hershberger, Kian K.; Bronstein, Lyudmila M. (Frontiers in Chemistry, 2020)
Theranostics is a fast-growing field due to demands for new, efficient therapeutics which could be precisely delivered to the target site using multimodal imaging with enhancing auxiliary actions. In this review article we discuss theranostic nanoplatforms containing polymers and magnetic nanoparticles along with other components. Magnetic nanoparticles allow for both diagnostic and therapeutic (hyperthermia) capabilities, while polymers can be reservoirs for drugs and are easily functionalized for cell targeting. We focus on the most important design strategies to achieve optimal theranostic effects as well as the roles of different components included in theranostics, reviewing the literature from the last five years.